Roots of change: intergenerational cycle of adolescent fatherhood in rural Jharkhand and Odisha - Jagadeesh, Bharath; Minj, Rohit Ranjan Paul; Bhatnagar, Anuj (International Journal Of Community Medicine And Public Health, 2023)
Background: Numerous studies have documented an intergenerational cycle of adolescent motherhood, wherein daughters of adolescent mothers are more likely to follow suit. This pattern may result from biological predisposition, heritable attitudes, or the socioeconomic environment influenced by early childbirth. Surprisingly, the same cycle among young fathers remains unexplored in India. This research paper seeks to enrich the existing body of knowledge by shedding light on the intergenerational cycle of adolescent fatherhood in the rural Jharkhand and Odisha, possibly as a first of its kind study. Methods: A case control study was conducted between June 2023 to August 2023 amongst adolescent males residing in rural areas of Jharkhand and Odisha states with sample size of 228 using multi-stage sampling technique. Results: The study did not reveal statistically significant association between adolescent fathers of this generation and adolescent fathers or adolescent mothers of previous generation, unlike in the case of adolescent mothers. Conclusions: To address adolescent reproductive sexual Health challenges in rural Jharkhand and Odisha effectively, it is imperative to emphasize targeted educational campaigns with cultural sensitivity, actively involve adolescent males and maintain a steadfast long-term commitment to fostering cultural transformation.